Confronting the wildlife trade through public education at zoological institutions in Chengdu, P.R. China. Issue 2 (5th February 2018) - Clayton, Susan; Bexell, Sarah; Ping, Xu; Zhihe, Zhang; Jing, Li Wen; Wei, Chen Hong; Yan, Hu
Abstract : The wildlife trade poses substantial threats to global biodiversity. China is a significant source of threatened species and also a market for wildlife products. Zoological parks (zoos), which are a popular leisure attraction in China as elsewhere, are increasingly conceptualized as places to educate visitors about both animals and environmental threats more generally. This paper reports on an attempt to inform Chinese zoo visitors about the threats presented by the wildlife trade, and about the opportunity to take personal actions to help protect wildlife. Results from a baseline survey of attitudes among 524 adult visitors to animal exhibits in Chengdu, China showed a high degree of concern about wildlife paired with a lack of confidence about what could be done. A sense of connection to nature, along with a perception of personal efficacy, were the strongest predictors of concern about the wildlife trade. Based in part on these results, an informational exhibit was designed and implemented in two locations in Chengdu. A survey of 533 visitors to assess the impact of the new exhibit showed that connection and perceived efficacy continued to predict concern, and that talking about the exhibit was associated with increased knowledge and concern. Though causality cannot be definitively concluded, results suggest that zoos have the potential to influence attitudes and perceived norms regarding the wildlife trade. By affirming the importance of a feeling of connection, the findings indicate that animal facilities may have an important role in fostering the human relationship to the natural world.